2019
DOI: 10.3389/fonc.2019.00989
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Signaling in Cancer: Its Functions and Role as a Therapeutic Target

Abstract: Cadherin family includes lists of transmembrane glycoproteins which mediate calcium-dependent cell-cell adhesion. Cadherin-mediated adhesion regulates cell growth and differentiation throughout life. Through the establishment of the cadherin-catenin complex, cadherins provide normal cell-cell adhesion and maintain homeostatic tissue architecture. In the process of cell recognition and adhesion, cadherins act as vital participators. As results, the disruption of cadherin signaling has significant implications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 214 publications
1
118
2
8
Order By: Relevance
“…On the contrary, they promote the generation of T regs [116]. Accordingly, it was found that in DCs β-catenin, an important transcription factor downstream E-cadherin signaling pathway [117], is essential for the expression of immunosuppressive mediators and for the stimulation of T regs and the concomitant suppression of effector T cells [118]. Moreover, it has also been proposed that dendritic cells may contribute to sustaining an immunosuppressive tumor microenvironment after up-regulation of E-cadherin on their membrane, a phenomenon triggered by soluble factors secreted by tumor cells [119].…”
Section: E-cadherin and The Immune Systemmentioning
confidence: 99%
“…On the contrary, they promote the generation of T regs [116]. Accordingly, it was found that in DCs β-catenin, an important transcription factor downstream E-cadherin signaling pathway [117], is essential for the expression of immunosuppressive mediators and for the stimulation of T regs and the concomitant suppression of effector T cells [118]. Moreover, it has also been proposed that dendritic cells may contribute to sustaining an immunosuppressive tumor microenvironment after up-regulation of E-cadherin on their membrane, a phenomenon triggered by soluble factors secreted by tumor cells [119].…”
Section: E-cadherin and The Immune Systemmentioning
confidence: 99%
“…The process which enables tumor cells to achieve migration and invasion is called epithelial-mesenchymal transition (EMT) and represents a driving force in tumorigenesis [23]. In the course of EMT, essential proteins for epithelial cell-cell adhesion, such as E-cadherin, are downregulated, thus weakening epithelial tissue integrity and polarization of epithelial cell layers [24]. Under normal circumstances, detached epithelial cells undergo apoptosis, a phenomenon termed anoikis.…”
Section: Introductionmentioning
confidence: 99%
“…Vimentin, a mesenchymal-specific IFs protein, is a distinct feature of EMT [53]. The EMT activation is correlated with molecular changes as shifts in cadherins expression [54], cytokeratin loss, vimentin and collagen increased expressions [53,55]. Moreover, PI3K-AKT pathway are essential to maintain the CSC-like phenotype and EMT characteristics in breast cancer cells [56].…”
Section: Discussionmentioning
confidence: 99%